The value of endothelial dysfunction markers in the pathogenesis of morphological and functional changes of chorion in women with previous reproductive loss - O S Pobedinskaya; - Ajeni Daniel Olusola; I M Ordiianc (RUDN Journal of Medicine, 2013)
The value of the markers of endothelial dysfunction in the pathogenesis of morphofunctional changes chorion in women with early reproductive losses. The principal causes of intravascular cytotrophoblast invasion insufficiency are: reduction of NOs level and E-celektine level in serum samples and a rise in Endothelin-1 levels, which correlates with the changes of circulating population of platelets — depressed numbers of platelets at rest, rising of quantity of degenerated platelets which leads to a low vascular resistance in the uterine, spiral and radial arteries. Definition of markers of endothelial dysfunctions, changes in parameters of the morpho-functional states of platelets, increase in the quantity of degenerated platelets and ultrasonic estimation of the blood flow in the uterine, spiral and radial arteries may serve as prognostic criteria to determine the end result of early pregnancy losses.